THE IMPACT OF HUMAN ACTIVITIES ON ENVIRONMENTAL SUSTAINABILITY - Mohammed Jabar Odah Inbit; Mohamed abdulhassan eliwi alkolany; Ahmed Abd Ali Kazem; Hussain Hamza Hussein; Raed Abd AL-kadum mageed Brism (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
-